The Implementation of Antam Gold Installment Financing in Increasing Profitability at Bank Syariah Indonesia Muara Teweh Branch (IAIN Kudus, 2025)
Antam gold installment financing is a long-term investment that continues to increase every year. Based on data found by researchers during an internship in September 2024, 243 customers participated in gold installment financing, which has an impact on increasing bank profitability. This financing is based on DSN-MUI Fatwa No. 77/DSN-MUI/VI/2010, which permits the sale and purchase of gold without cash as long as it is used for investment, not as a medium of exchange. This study aims to determine the implementation of Antam gold installment financing at Bank Syariah Indonesia (BSI) KCP Muara Teweh and its contribution to bank profitability. The method used is a descriptive qualitative approach with data collection techniques through observation, interviews with five informants, as well as documentation and secondary data from BSI KCP Muara Teweh which were analyzed descriptively. The results show that the implementation of Antam gold installment financing at BSI KCP Muara Teweh requires customers to pay a down payment of 5% of the gold price using a murabahah (sale and purchase) contract and a rahn (pawn) contract as collateral. Supported by an effective marketing strategy, this financing has increased customer numbers and profitability, as reflected in a monthly ROA of 0.41% and ROE of 42.23%. Therefore, Antam gold installment financing has proven to positively contribute to increased profitability at BSI KCP Muara Teweh.